"Above all": The myth of 'dreams' as advertising tool - O'Halloran, Kay; Tan, S.; E, M.K.L. (Universitat De Valencia, 2013)
Advertising helps us to make sense of things. It validates consumer commodities and a consumer life-style by associating goods with personal and social meanings and those aspirations and needs which are not fulfilled in real life. We come to think that consuming commodities will give us our identities.